The cost effectiveness of pharmacological smoking cessation therapies in developing countries: a case study in the Seychelles. Issue 2 (2nd June 2004) - Gilbert, A R; Pinget, C; Bovet, P; Cornuz, J; Shamlaye, C; Paccaud, F
Abstract : Objective: To examine the incremental cost effectiveness of the five first line pharmacological smoking cessation therapies in the Seychelles and other developing countries. Design: A Markov chain cohort simulation. Subjects: Two simulated cohorts of smokers: (1) a reference cohort given physician counselling only; (2) a treatment cohort given counselling plus cessation therapy. Intervention: Addition of each of the five pharmacological cessation therapies to physician provided smoking cessation counselling. Main outcome measures: Cost per life-year saved (LYS) associated with the five pharmacotherapies. Effectiveness expressed as odds ratios for quitting associated with pharmacotherapies. Costs based on the additional physician time required and retail prices of the medications. Results: Based on prices for currently available generic medications on the global market, the incremental cost per LYS for a 45 year old in the Seychelles was US$599 for gum and $227 for bupropion. Assuming US treatment prices as a conservative estimate, the incremental cost per LYS was significantly higher, though still favourable in comparison to other common medical interventions: $3712 for nicotine gum, $1982 for nicotine patch, $4597 for nicotine spray, $4291 for nicotine inhaler, and $1324 for bupropion. Cost per LYS increased significantly upon application of higher discount rates, which may be used to reflect relatively high opportunity costs for health expenditures in developing countries with highly constrained resources and high overall mortality. Conclusion: Pharmacological cessation therapy can be highly cost effective as compared to other common medical interventions in low mortality, middle income countries, particularly if medications can be procured at low prices.